Extracellular Vesicles Derived From Citrus sinensis Modulate Inflammatory Genes and Tight Junctions in a Human Model of Intestinal Epithelium - Bruno, Stefania Paola; Paolini, Alessandro; D'Oria, Valentina; Sarra, Angelo; Sennato, Simona; Bordi, Federico; Masotti, Andrea (Frontiers in Nutrition, 2021)
It is widely acknowledged that mammalian exosomes (or extracellular vesicles), have a key role in intercellular communication, owing to the presence of various bioactive molecules such as lipids, proteins, and microRNAs within their inner compartment. Most recently, the discovery of extracellular vesicles isolated from edible plants (such as vegetables and fruits) and their similarity in terms of size and content with exosomes has opened new perspectives on possible intercellular communication and regulation of important biological processes in which these vesicles are involved. It is also well-known that a balanced diet rich of fruits and vegetables (i.e., the Mediterranean diet) can contribute to maintain a “healthy gut” by preserving the intestinal epithelial barrier integrity and avoid that inflammatory stimuli that can alter homeostasis. In our study, we optimized a method to isolate extracellular vesicles from the orange juice (Citrus sinensis) (CS-EVs), and we characterized their morphology and behavior when in contact with the intestinal epithelium. We showed that CS-EVs are stable in a simulated gastrointestinal environment and are absorbed by intestinal cells without toxic effects, as expected. Furthermore, we demonstrated that CS-EVs can alter the gene expression of several genes involved in inflammation (i.e., ICAM1 and HMOX-1) and tight junctions (i.e., OCLN, CLDN1, and MLCK), contributing to limit inflammatory stimuli and restore a functional barrier by increasing the tight junction OCLN protein. Therefore, our study emphasizes the relevant role of fruit-derived extracellular vesicles in modulating important biological processes and maintaining a healthy intestinal epithelium, ultimately promoting human health and well-being.